2011
DOI: 10.1016/j.cortex.2011.02.014
|View full text |Cite
|
Sign up to set email alerts
|

The impairment of emotion recognition in Huntington’s disease extends to positive emotions

Abstract: Patients with Huntington’s Disease are impaired in the recognition of emotional signals. However, the nature and extent of the impairment is controversial: It has variously been argued to be disgust-specific (Sprengelmeyer et al., 1996; 1997), general for negative emotions (Snowden, et al., 2008), or a consequence of item difficulty (Milders, Crawford, Lamb, & Simpson, 2003). Yet no study to date has included more than one positive stimulus category in emotion recognition tasks. We present a study of 14 Huntin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…That is, there was nothing specific about the emotional content of the faces that differentiated the groups. This interpretation is consistent with a recent study assessing emotional response to auditory sounds in HD participants (Robotham et al, 2011), which reported performance decrements in HD across all emotion types, including positive valence sounds. However, given the use of a different modality (auditory as opposed to visual), and the lack of comparison between emotional and non-emotional sounds, it is difficult to translate the relevance to emotional face processing.…”
Section: Discussionsupporting
confidence: 92%
“…That is, there was nothing specific about the emotional content of the faces that differentiated the groups. This interpretation is consistent with a recent study assessing emotional response to auditory sounds in HD participants (Robotham et al, 2011), which reported performance decrements in HD across all emotion types, including positive valence sounds. However, given the use of a different modality (auditory as opposed to visual), and the lack of comparison between emotional and non-emotional sounds, it is difficult to translate the relevance to emotional face processing.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that functional MRI indices may be more sensitive than behavioural indices in tracking altered emotion processing in Huntington's disease, and raise the further possibility that the use of alternative, more finely differentiated stimuli might however reveal hitherto largely undetected deficits in processing positive-valence facial expressions. The detection of impaired recognition of vocal expressions of positive emotions in Huntington's disease in one previous study (Robotham et al , 2011) supports this assertion.…”
Section: Discussionsupporting
confidence: 68%
“…svPPA patients also have impaired comprehension of sarcasm based specifically on (primarily vocal) paralinguistic cues [24]. Additionally, HD patients show poor recognition of negative [12] as well as positive [25] vocal emotional signals. In contrast, AD patients’ ability to read emotions in both voice prosody and music is preserved [26].…”
Section: Perception Of Social and Emotional Signalsmentioning
confidence: 99%